Effect of continuous and partial reinforcement on the acquisition and extinction of human conditioned fear - Grady, Ashley K; Bowen, Kenton H; Hyde, Andrew T; Totsch, Stacie K; Knight, David C (Behavioral neuroscience, 2016)
Extinction of Pavlovian conditioned fear in humans is a popular paradigm often used to study learning and memory processes that mediate anxiety-related disorders. Fear extinction studies often only pair the conditioned stimulus (CS) and unconditioned stimulus (UCS) on a subset of acquisition trials (i.e., partial reinforcement/pairing) to prolong extinction (i.e., partial reinforcement extinction effect; PREE) and provide more time to study the process. However, there is limited evidence that the partial pairing procedures typically used during fear conditioning actually extend the extinction process, while there is strong evidence these procedures weaken conditioned response (CR) acquisition. Therefore, determining conditioning procedures that support strong CR acquisition and that also prolong the extinction process would benefit the field. The present study investigated 4 separate CS-UCS pairing procedures to determine methods that support strong conditioning and that also exhibit a PREE. One group (C-C) of participants received continuous CS-UCS pairings; a second group (C-P) received continuous followed by partial CS-UCS pairings; a third group (P-C) received partial followed by continuous CS-UCS pairings; and a fourth group (P-P) received partial CS-UCS pairings during acquisition. A strong skin conductance CR was expressed by C-C and P-C groups but not by C-P and P-P groups at the end of the acquisition phase. The P-C group maintained the CR during extinction. In contrast, the CR extinguished quickly within the C-C group. These findings suggest that partial followed by continuous CS-UCS pairings elicit strong CRs and prolong the extinction process following human fear conditioning.